RESPON KOMBINASI PERLAKUAN PUPUK NPK DAN PERLAKUAN BENIH DENGAN PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI HITAM VARIETAS JELITENG - hasmi, Idrus; Jaenudin , Achmad; Sungkawa, I (Agroswagati : Jurnal Agronomi, 2021)
This research is a research on improving the technology of rice cultivation of Jeliteng varieties through the application of the addition of a combination of NPK fertilizer and biological fertilizer in seed treatment. The research was carried out at the KP Pusakanagara Installation ICRR in MT I 2022 using a Randomized Block Design (RCBD) with 3 replications with a combination of treatments : 1) No seed treatment (without biological fertilizer) + 0 kg/ha NPK (H0N0), 2) No seed treatment (without biological fertilizer) + 200 kg/ha NPK (H0N1), 3) No seed treatment (without biological fertilizer) + 300 kg/ha NPK (H0N2), 4) No seed treatment (without biological fertilizer) + 400 kg/ha NPK (H0N3), 5) Dosage of biological fertilizer DSE type 1, 500 g/25 kg seeds + 0 kg/ha NPK (H1N0), 6) Dosage of biological fertilizer DSE type 1, 500 g/25 kg seeds + 200 kg/ha NPK (H1N1), 7) Dosage of biological fertilizer DSE type 1, 500 g/25 kg seeds + 300 kg/ha NPK (H1N2), 8) Dosage of biological fertilizer DSE type 1, 500 g/25 kg seeds + 400 kg/ha NPK (H1N3), 9) Dosage of biological fertilizer DSE type 2, 500 g/25 kg seed + 0 kg/ha NPK (H2N0), 10) Dosage of biological fertilizer DSE type 2, 500 g/25 kg seed + 200 kg/ha NPK (H2N1), 11) Dosage of biological fertilizer DSE type 2, 500 g/25 kg seeds + 300 kg/ha NPK (H2N2), 12) Dosage of biological fertilizer DSE type 1, 500 g/25 kg seed + 400 kg/ha NPK (H2N3). The results showed that the combination of NPK fertilizer treatment and seed treatment with biological fertilizers had a significant effect on plant height growth, number of tillers and leaf greenness value. The highest plant height was found in H0N3, namely 58.11 cm at 35 DAP, 69.75 cm at 50 DAP and 100.72 cm at 65 DAP, The highest number of tillers were found in H1N3 with 6.5 tillers at 25 DAP, 13.89 at 35 DAP and 14.19 at 50 DAP, and the greenery value of the leaves the highest value was found in H0N3 which was 38.80 at the age of 25 DAP, H2N1 was 40.00 at 35 DAP and H2N3 was 46.07 at the age of 50 DAP. The combination of NPK fertilizer treatment and seed treatment with biological fertilizers had no significant effect on yield, number of panicles per clump, number of grain per panicle, weight of 1000 grains of grain (g) and percent of grain content (%)